Efficient photocatalytic hydrogen evolution mediated by defect-rich 1T-PtS2 atomic layer nanosheet modified mesoporous graphitic carbon nitride. Issue 32 (29th July 2019) - Liu, Jinyuan; Xu, Hui; Yan, Jia; Huang, Jihua; Song, Yanhua; Deng, Jiujun; Wu, Jingjie; Ding, Cheng; Wu, Xiangyang; Yuan, Shouqi; Li, Huaming
Abstract : The intimate contact heterostructures between defect-rich 1T-PtS2 atomic layer nanosheets and MCN have been constructed, which promote the effective separation of photogenerated carriers, thus improving the photocatalytic hydrogen production performance. Abstract : The PtS2 material is mainly considered an optoelectronic and thermoelectric material which has not been applied in the photocatalytic field. Herein, we deposited ultrathin PtS2 nanosheets onto mesoporous graphitic carbon nitride (MCN) to construct ultrathin PtS2 /MCN composites toward the photocatalytic hydrogen evolution reaction (HER). Defect engineering was introduced into the PtS2 atomic layers by a simple method of liquid phase exfoliation (LPE) using bath ultrasonication. The defect-rich 1T-PtS2 atomic layer nanosheets were uniformly dispersed on the surface of MCN, and intimate contact heterostructures were constructed. The photocatalytic HER performances of PtS2 co-catalyst nanosheets with different thicknesses were also investigated. The MCN modified with 1 wt% defect-rich 1T-PtS2 atomic layer nanosheets exhibited the highest photocatalytic HER activity. This is attributed to the formation of close heterostructures between PtS2 and MCN that can promote the transfer and separation of photogenerated charge carriers. This work provides new opportunities for the rational design of controllably structured hydrogen evolution photocatalysts with improved catalytic properties for sustainable energy applications.